Еfficiency of Оrganic and Іntensive Watermelon Growing Technology - Inozemtsev, Mykola; Romanova, Tetiana; Romanov, Olekcii; Ivanova, Iryna; Shkinder-Barmina, Anna; Іноземцев, Микола Дмитрович; Романова, Тетяна Анатоліївна; Романов, Олексій Васильович; Іванова, Ірина Євгенівна; Шкіндер-Барміна, Анна Миколаївна (Вінниця : ТОВ «ТВОРИ», 2026)
EN: Purpose. To determine the effectiveness of organic and intensive watermelon cultivation technologies under the conditions of the Steppe zone of Ukraine. Methods. The research was conducted at the “Shchedryi Lan” farming enterprise located in the Kramatorsk district of Donetsk region. The experimental design included three treatments: control (watermelon cultivation without fertilizers and plant protection products), intensive cultivation technology, and organic cultivation technology. The watermelon hybrid Farao F1 was grown by the seedling method with a planting scheme of 140 × 70 cm (10.2 thousand plants per hectare) using drip irrigation and soil mulching with plastic film. Results. The article presents the results of evaluating the effectiveness of organic and intensive watermelon cultivation technologies and their influence on plant productivity, fruit yield, biochemical composition, and economic performance. Conclusions. In terms of plant productivity, the organic cultivation approach was inferior to the intensive technology. Under organic cultivation, plants formed on average one fruit weighing 5.8 kg, whereas intensive technology ensured the formation of 2.8 fruits per plant with an average weight of 10 kg. Intensive cultivation technology provided the highest watermelon yield, reaching 83.3 t/ha, while under organic cultivation the yield amounted to 31.2 t/ha. Differences between cultivation technologies in fruit dry matter content (8.0–9.2%) and total sugar content (7.2–7.5%) were insignificant. However, the organic cultivation technology resulted in fruits with a significantly higher vitamin C content (9.8 mg/100 g) and a lower nitrate concentration (35.0 mg/kg) compared with the intensive technology (60.0 mg/kg). The higher watermelon yield obtained under intensive cultivation ensured the maximum profit level (UAH 780.0 thousand/ha), exceeding that of the organic technology (UAH 528.88 thousand/ha). At the same time, the lower production costs under organic cultivation (UAH 170.0 thousand/ha) resulted in a similar production cost level for both technologies (UAH 5.20–5.45/kg). When organic products were sold with a 40% price premium, the highest profitability level was recorded for the organic technology (311.0%), whereas under intensive cultivation this indicator reached 150.0%. /// UA: Встановлення ефективності органічної та інтенсивної технологій вирощування кавуна в умовах Степу України. Методи. Дослідження проведено на базі фермерського господарства «Щедрий лан», розташованого в Краматорському районі Донецької області. Схема досліду включала три варіанти: контроль (вирощування кавуна без застосування добрив і засобів захисту рослин); інтенсивна та органічна технології вирощування. Гібрид кавуна Фарао F1 вирощували розсадним способом за схемою висадки рослин 140×70 см (10,2 тис. шт./на га) з використанням крапельного зрошування та мульчування ґрунту плівкою. Результати. У статті представлено результати визначення ефективності органічної та інтенсивної технологій вирощування кавуна з впливом на показники продуктивності рослин, урожайністю плодів та їх біохімічним складом, економічними параметрами вирощування. Висновки. За рівнем продуктивності рослин органічні підходи вирощування кавуна поступаються інтенсивній технології. При цьому на рослині формується в середньому один плід х масою 5,8 кг, тоді як за інтенсивної технології формується 2,8 плоди/рослину з середньою масою 10 кг. Інтенсивна технологія вирощування забезпечує максимальну урожайність кавуна на рівні 83,3 т/га, тоді як за органічних підходів урожайність становила 31,2 т/га. За вмістом в плодах сухої речовини (8,0-9,2 %) та загального цукру (7,2-7,5 %) між технологіями вирощування відмінність незначна. Використанням органічної технології вирощування зумовлює формування плодів з істотно вищим вмістом вітаміну С (9,8 мг/100 г) та нижчою кількістю нітратів (35,0 мг/кг), відносно інтенсивної технології вирощування (60,0 мг/кг). Більш високий рівень урожайності кавуна за інтенсивних підходів вирощування зумовлює отримання максимального рівня прибутку (780,0 тис. грн./га), що перевищує показник за органічної технології вирощування (528,88 тис. грн./га). Але відносно нижчий рівень витрат на вирощування за органічної технології (170,0 тис. грн./га) зумовлює рівень собівартості продукції за обох технологічних підходів на одному рівні (5,20-5,45 грн./кг). За умови продажу органічної продукції з націнкою 40% в дослідженнях зафіксовано більш високий рівень рентабельності виробництва за органічної технології (311,0 %), тоді як за інтенсивних підходів вирощування даний показник становив 150,0 %.
Ефективність органічної та інтенсивної технології вирощування кавуна
Keywords: watermelon; plant productivity; yield; biochemical composition of products; economic effi ciency; кавун; продуктивність рослин; урожайність; біохімічний склад продукції; економічна ефективність